2008
DOI: 10.1124/dmd.108.021428
|View full text |Cite
|
Sign up to set email alerts
|

Expression of UGT1A and UGT2B mRNA in Human Normal Tissues and Various Cell Lines

Abstract: ABSTRACT:UDP-glucuronosyltransferases (UGTs) are major phase II drug metabolism enzymes that catalyze the glucuronidation of numerous endogenous and exogenous compounds. UGTs are divided into two families, UGT1 and UGT2, based on evolutionary divergence and homology. Nine UGT1A and seven UGT2B functional isoforms have been identified in humans. Glucuronidation occurs mainly in liver but also in various extrahepatic tissues, possibly affecting the pharmacokinetics. In the present study, we comprehensively deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
227
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 251 publications
(247 citation statements)
references
References 14 publications
19
227
1
Order By: Relevance
“…UGT1A10 was considered an extrahepatic UGT that is mainly expressed in the intestine (Strassburg et al, 1997(Strassburg et al, , 1998(Strassburg et al, , 1999Mojarrabi and Mackenzie, 1998;Cheng et al, 1999;Zheng et al, 2002). However, in a recent study, low expression levels of UGT1A10 were detected in liver and hepatocytes (Li et al, 2007;Nakamura et al, 2008). Based on the latter, it might be speculated that low expression levels of UGT1A10 that were not detected previously could also occur in the brain.…”
mentioning
confidence: 84%
“…UGT1A10 was considered an extrahepatic UGT that is mainly expressed in the intestine (Strassburg et al, 1997(Strassburg et al, , 1998(Strassburg et al, , 1999Mojarrabi and Mackenzie, 1998;Cheng et al, 1999;Zheng et al, 2002). However, in a recent study, low expression levels of UGT1A10 were detected in liver and hepatocytes (Li et al, 2007;Nakamura et al, 2008). Based on the latter, it might be speculated that low expression levels of UGT1A10 that were not detected previously could also occur in the brain.…”
mentioning
confidence: 84%
“…In addition to genetic polymorphism, the induction by environmental and/or diet would be casual factors of the variability of the UGT expression (Nakamura et al, 2008). Moreover, it was shown that UGT expression was restricted to certain cell types or regions in an organ by immunohistochemical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is important to stress that a larger and independent group, which includes women with schizophrenia, must be tested, we have chosen the male gender due to the possible confounding of female hormonal states at the time of blood sampling and the effect of contraceptives, which influence on the gene expression profiles (Nakamura et al, 2008). Besides, we used a customised microarray platform, with enrichment for neurodevelopment genes, due to their involvement with the disease (Palha and Goodman, 2006;Ruano et al, 2008) and the current accepted view that schizophrenia is a neurodevelopment disorder in which genes and environment interplay for disease onset and progression.…”
Section: Discussionmentioning
confidence: 99%